Translocality and the Class Conditions of Filipino Nurse Migrants in the Republic of Ireland - Trinidad, Arnie Cordero (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2024)
The rise in the number of international labour migrants and their situatedness in and attachments to multiple locations are creating complex class conditions for migrant labour, which are only beginning to be understood in research through the use of a translocal frame. For a long time, studies on migrants have been dominated by methodological nationalism that uses the nation as the contextual background for studies of social processes. In time, this was replaced by the transnational frame of reference in recognition of globalisation and the breaching of the national boundaries with migration. However, there is now greater acknowledgement of the role of localities in the lives of migrants and social processes surrounding them. While they exist in the transnational space, they are situated and connected to national, regional, institutional, and local spaces. Moreover, they are connected to social networks that are nested in specific geographical locations that impinge on their lives. The study explores the relationship between the translocal space and the class conditions of migrant workers. It aims to establish how multilocal connections are impacting or impinging on the class conditions of migrant workers. Using Filipino migrant nurses in Ireland as a case study, the work examines the consequences of the translocal locations and connections of migrants to their class conditions related to social mobility, with-in class inequalities, life chances and opportunities, and occupational conditions. To frame these class processes occurring in the translocal space, the work draws from the concepts and theories on occupational class,socioeconomic class, class analysis, and translocality. The research uses a case study mixed methods design where a ¿parent case study¿ method was employed with a ¿nested mixed methods design¿ composed of a survey, semi-structured interviews, and qualitative social network analysis embedded in the interview guide. A total of 418 nurses all over Ireland participated in the survey, while 61 nurses were interviewed for the qualitative portion of the research. The movement to a developed state expectedly resulted in positive improvements in the occupational class conditions of migrants in terms of salaries, benefits, patient numbers, and other similar variables. Interestingly, their work conditions in the Philippines and Ireland share fundamental similarities due to the two states¿ subscription to neoliberal policies of privatisation and fiscal austerity measures. The difference lies in the scope and magnitude of the work issues they are facing. The divergences in their conditions are brought about by their diverse institutional affiliations and the fiscal situation of the countries. Next, while migration facilitates upward social mobility, the class conditions of the family back home determine the migrants¿ life chances and their ability to fully enjoy their middle-class status in the host country. The advantage of nurses from more affluent families in the Philippines enables them to fulfil their class goals ahead of nurses who maintain familial responsibilities back home, thus reproducing some of the social hierarchies back home in the host country. To balance responsibilities back home and their desire to live a comfortable middle-class life in Ireland, some nurses choose to live and work in fringe communities to enjoy lower costs of living, thus enabling them to pursue their middle-class goals. In the arena of work, state policies create similar work conditions in fringe communities to those found in major Irish cities. However, the fringe localities also create unique work conditions as services in smaller hospitals in rural towns are shut down and the hospitals are defunded. Lastly, the various kindship networks of migrants play different roles in facilitating or destabilising the economic stability of migrant workers. The thesis contributes to the conceptualization of class using a translocal frame and in uncovering some of the complexities of class in the transnational migration field.
APPROVED
Keywords: translocality; social class; migration; Filipino nurses; Ireland